Relationship of Matrix Metalloproteinase-1 with Clinical and Radiological Features of Pulmonary Tuberculosis Co-infection of Human Immunodeficiency Virus Patients - Prayudianto, Roykhan; Ayu Yuli Gayatri, Anak Agung (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: The co-infection of pulmonary Tuberculosis (TB) in Human Immunodeficiency Virus (HIV) patients continues to pose a global health challenge. Mycobacterium tuberculosis (Mtb) and HIV can synergize, thereby worsening the condition of patients. Matrix metalloproteinase (MMP) is known to play a role in the pathogenesis of HIV-TB. Clinical and radiological presentations of M. tuberculosis patients show destruction of the extracellular matrix of the lungs involving protease actions, particularly matrix metalloproteinases (MMPs), one of which is MMP-1, resulting in the degradation of the lung's structural fibrils. Objective: The aim of this study is to investigate the relationship between MMP-1 and the clinical and radiological manifestations in the co-infection of pulmonary TB in HIV patients. Method: The research sample comprised 34 individuals. The median age of the study subjects was 41.5 (21 – 67) years, with the majority being <50 years old (64.7%) and male (70.6%). Result and Discussion: The cut-off value for MMP-1 level was determined using ROC curve analysis, where a level of 2.125 pg/mL demonstrated good sensitivity and specificity in predicting clinical symptoms and radiological findings. Mann-Whitney test revealed a significant difference in MMP-1 neko77 between positive and negative groups for both clinical symptoms (p<0.05) and radiological findings (p<0.01). Fisher's Exact test supported the association between MMP-1 levels and clinical symptoms (PR=1.929; CI95%=0.864 – 4.306; p=0.012) as well as radiological findings (PR=5.571; CI95%=0.928 – 33.441; p<0.001). Multivariate analysis indicated that variables other than MMP-1 level did not influence clinical symptoms and radiological findings in this study. Conclusion: In conclusion, MMP-1 levels are associated with clinical symptoms and radiological features of pulmonary TB coinfection in HIV patients. The MMP-1 cutoff level of 2.125 pg/mL increases the risk of clinical symptoms and radiological findings in patients